2011
DOI: 10.1007/s12160-011-9324-7
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of a Telephone-Delivered Exercise Intervention for Non-urban Dwelling Women Newly Diagnosed with Breast Cancer: Exercise for Health

Abstract: Given the limited availability of physical activity programs for non-urban women with breast cancer, results provide strong support for feasibility and modest support for the efficacy of telephone-delivered interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
220
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(223 citation statements)
references
References 44 publications
2
220
0
1
Order By: Relevance
“…Future research should focus on delivery modalities that decrease burden and increase acceptability in a larger proportion of caregivers (e.g., those who are feeling too overwhelmed to attend in-person intervention sessions). Telephone interventions have been successful in providing efficacious psychosocial interventions for cancer patients and caregivers [36][37][38][39] and recent research on web-based interventions [40][41][42] and interventions using Smart phones and other delivery platforms [43] appear promising. These interventions provide more flexibility and cancer caregivers report they would reduce burden [44].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should focus on delivery modalities that decrease burden and increase acceptability in a larger proportion of caregivers (e.g., those who are feeling too overwhelmed to attend in-person intervention sessions). Telephone interventions have been successful in providing efficacious psychosocial interventions for cancer patients and caregivers [36][37][38][39] and recent research on web-based interventions [40][41][42] and interventions using Smart phones and other delivery platforms [43] appear promising. These interventions provide more flexibility and cancer caregivers report they would reduce burden [44].…”
Section: Discussionmentioning
confidence: 99%
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Two rcts compared various settings for interventions and found that the beneficial effects were greater when sessions were supervised, both in groups and by telephone 39,43 . One rct found a significant linear trend between an increase in mets performed per week and an improved qol score for all patients in the study 54 .…”
Section: Exercising In Group or Supervised Settingmentioning
confidence: 99%
“…Fourteen systematic reviews [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] found an improvement in qol for people with cancer participating in an exercise intervention during the active treatment or post-treatment periods (Table v). Of the sixteen rcts involving patients in active treatment [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , seven reported significant differences between the intervention and control groups (Table vi) 23,24,26,[31][32][33]36 . In the thirteen posttreatment intervention studies [38][39][40][41][42][43][44]…”
Section: Qol and Muscular And Aerobic Fitnessmentioning
confidence: 99%
“…Seven 26,28,34,35,40,46,50 did not report on adverse events at all. Three rcts 25,41,44 reported adverse events that were deemed not to be related to the intervention; two 36,38 reported events that were attributable to the intervention (3 patients experienced muscle soreness, and 2 experienced musculoskeletal injury).…”
Section: Commentsmentioning
confidence: 99%